Frequency converter of gas concentration in transistor structure with negative resistance - Osadchuk, A.V.; Osadchuk, V.S.; Osadchuk, I.A.; Seletska, O.O. (Radiotekhnika, 2017)
A frequency converter of gas concentration with a resistive element MEMC MiCS 6814, which determines the concentration of combustible gases, is presented. The dependences of the active and reactive components of the impedance of the gas concentration converter on the supply and control voltages and on the change in the gas concentration have been calculated and experimentally confirmed. Analytical expressions for the transformation function and the sensitivity equation are obtained. The sensitivity of the converter varies from 645 to 175 Hz / ppm in the concentration range from 1 to 1500 ppm, and decreases significantly with an increase in the propane concentration from 1500 ppm to 9000 ppm, and is from 175 Hz / ppm to 48 Hz / ppm.